Chemical profiling of essential oils: Investigations into modulating milk production in dairy cows using in silico methods - GÖZE, İsmihan; KAYMAK, Sibel; VURAL, Nilüfer (Sciences of Phytochemistry, 2024)
This study aimed to assess the biological and biotherapeutic activities of essential oils derived from the medicinal plants Tanacetum vulgare L., Myrtus communis L. subsp. communis L., and Pimpinella flabellifolia (Boiss.) Benth. Et Hook. ex Drude. Plant samples were systematically collected from the Sivas region of Türkiye. Subsequently, essential oils were extracted using a Clevenger-type apparatus, and their compositions were assessed by gas chromatography–mass spectrometry (GC-MS) analysis. Then, antioxidant activities of the essential oil samples were investigated using β-carotene-linoleic acid and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. Furthermore, the antimicrobial activity of these species was assessed via the disc diffusion assay. Finally, the potential effects of the essential oil compositions from these plants on milk production in dairy cows were analyzed through in-silico methods.